A general maximum energy efficiency tracking scheme for domino wireless power transfer systems with quasi-load-independent outputs - Wang, Kaiyuan (2024)
This article presents a double-layer pulsewidth pulse-frequency based optimal control (PWPFC) in achieving maximum energy efficiency tracking (MEET) and quasi-load-independent (QLI) constant current (CC) and constant voltage (CV) outputs for domino wireless power transfer (WPT) systems with full considerations of equivalent series resistances. The proposed hierarchical control, which can be implemented using inexpensive digital controllers, is applied to the primary-side inverters based on the measured output current, output voltage, and phase angle of the receiver current via infrared communication. The upper layer (i.e., stage-I) of the PWPFC is a reference selection algorithm to provide references of operating frequencies and duty ratios for the tracking algorithm of the lower layer (i.e., stage-II). To ensure accurate tracking, a hill-climbing method is adopted to regulate the operating frequency of practical domino WPT systems with parasitic components and disturbance. Experimental results have verified the effectiveness of the proposed PWPFC in regulating domino WPT systems with MEET and QLI CC and CV outputs under various loads, compensation networks, and initial frequency conditions.